2016
DOI: 10.1104/pp.16.00420
|View full text |Cite
|
Sign up to set email alerts
|

The ROS Wheel: Refining ROS Transcriptional Footprints

Abstract: In the last decade, microarray studies have delivered extensive inventories of transcriptome-wide changes in messenger RNA levels provoked by various types of oxidative stress in Arabidopsis (Arabidopsis thaliana). Previous cross-study comparisons indicated how different types of reactive oxygen species (ROS) and their subcellular accumulation sites are able to reshape the transcriptome in specific manners. However, these analyses often employed simplistic statistical frameworks that are not compatible with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 75 publications
3
120
0
Order By: Relevance
“…DCF and PO1 signals accumulate in the nucleus, as demonstrated by DCF colocalization with Hoechst stain, where ROS plays a role by changing the activity of redox-sensitive transcription factors (Willems et al, 2016). DCF signal has been observed previously in the guard cell cytoplasm (Lee et al, 1999;Kwak et al, 2003;Chen and Gallie, 2004;Watkins et al, 2014;Xia et al, 2014;, but the images within this data set use an Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…DCF and PO1 signals accumulate in the nucleus, as demonstrated by DCF colocalization with Hoechst stain, where ROS plays a role by changing the activity of redox-sensitive transcription factors (Willems et al, 2016). DCF signal has been observed previously in the guard cell cytoplasm (Lee et al, 1999;Kwak et al, 2003;Chen and Gallie, 2004;Watkins et al, 2014;Xia et al, 2014;, but the images within this data set use an Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…RBOH-dependent release of ROS was also found to modulate fiber growth in cotton (Gossypium hirsutum; Zhang et al, 2016) and peroxule outgrowth from peroxisomes (Rodriguez-Serrano et al, 2016). Furthermore, the meta-analysis of ROS-linked transcriptomes by Willems et al (2016) identified AtRBOHF as central component in ROS-dependent regulation. These findings, together with earlier results, as summarized e.g.…”
Section: In This Focusmentioning
confidence: 99%
“…At least two new efforts have recently been made to follow up on this analysis and identify transcript expression signatures that define the response of plants to different types of ROS and their production site (Vaahtera et al, 2014;Willems et al, 2016). These studies refine our understanding of regulatory networks activated in response to the accumulation of ROS in different cellular compartments and cell types.…”
mentioning
confidence: 99%
“…Considering the highly reactive nature of ROS, a functional interaction between ROS and RLK signaling could arise in the apoplast. While transcriptomic responses to ROS are specific to the origin and type of ROS molecules (Vaahtera et al, 2014;Willems et al, 2016), it is unlikely that the properties of ROS alone can explain this signaling specificity. Instead, ROS signaling pathways can interact with parallel signaling cascades initiated by, for instance, the activation of RLKs (Figure 1) to fine-tune the signaling outcome.…”
Section: Rlks Mediate Apoplastic Ros Perception (Rlks Downstream Of Ros)mentioning
confidence: 99%
“…In plants, ROS exert control over metabolic regulation, development, pathogen defense, and responses to abiotic stimuli (Wrzaczek et al, 2013). As evident from transcriptomic responses (Vaahtera et al, 2014;Willems et al, 2016), plant cells meticulously sense ROS and trigger specific responses tailored to the type, concentration, and subcellular origin of ROS molecules. However, it is unclear how this signaling specificity is achieved.…”
Section: Introductionmentioning
confidence: 99%